Melanoma in Adolescents and Young Adults: Evaluation of the Characteristics, Treatment Strategies, and Prognostic Factors in a Monocentric Retrospective Study - Del Fiore, Paolo; Russo, Irene; Ferrazzi, Beatrice; Monico, Alessandro Dal; Cavallin, Francesco; Filoni, Angela; Tropea, Saveria; Russano, Francesco; Di Prata, Claudia; Buja, Alessandra; Collodetto, Alessandra; Spina, Romina; et al. (Frontiers in Oncology, 2021)
The “Veneto Cancer Registry” records melanoma as the most common cancer diagnosed in males and the third common cancer in females under 50 years of age in the Veneto Region (Italy). While melanoma is rare in children, it has greater incidence in adolescents and young adults (AYA), but literature offers only few studies specifically focused on AYA melanoma. The aim of this study was to describe the characteristics, surgical treatment, and prognosis of a cohort of AYA melanoma in order to contribute to the investigation of this malignancy and provide better patient care. This retrospective cohort study included 2,752 Caucasian patients (702 AYA and 2,050 non-AYA patients) from the Veneto Region who were over 15 years of age at diagnosis, and who received diagnosis and/or treatment from our institutions between 1998 and 2014. Patients were divided in adolescents and youth (15-25 years), young adults (26-39 years) and adults (more than 39 years) for the analysis. We found statistically significant differences in gender, primary site, Breslow thickness, ulceration, pathologic TNM classification (pTNM) stage and tumor subtype among the age groups. Disease-specific survival and disease-free survival were also different among the age groups. Our findings suggest that the biological behavior of melanoma in young people is different to that in adults, but not such as to represent a distinct pathological entity. Additional and larger prospective studies should be performed to better evaluate potential biological and cancer-specific differences between AYAs and the adult melanoma population.